1999
DOI: 10.1002/(sici)1097-0231(19990815)13:15<1580::aid-rcm679>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for replicate bacterial culture analysis

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS) was used to demonstrate the reproducibility of bacterial spectra collected on different days. The reproducibility of analysis by MALDI-MS of intact Escherichia coli and Bacillus atrophaeus is presented as a replicate culture study in which spectra were collected on ten different occasions over a three-month period and by two different operators. The analysis resulted in the detection of specific biomarkers in the m/z 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
95
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 15 publications
(13 reference statements)
4
95
0
Order By: Relevance
“…These differences might be due to the variability of the dried sample spot and/or to the partial protein degradation. These results are in agreement with observations of previous studies [14,16,20]. Using the statistical approach, the signal intensity differences between D0 and D2 (D0 -D2) as well as D0 and D6 (D0 -D6) are reported in Figure 4 for thirteen ions (8113 is the reference for rescaling).…”
Section: Reproducibility Testssupporting
confidence: 91%
See 1 more Smart Citation
“…These differences might be due to the variability of the dried sample spot and/or to the partial protein degradation. These results are in agreement with observations of previous studies [14,16,20]. Using the statistical approach, the signal intensity differences between D0 and D2 (D0 -D2) as well as D0 and D6 (D0 -D6) are reported in Figure 4 for thirteen ions (8113 is the reference for rescaling).…”
Section: Reproducibility Testssupporting
confidence: 91%
“…Thus, the sample preparation strategy adopted for MALDI-TOFMS of whole bacteria is crucial to improve this reproducibility. Indeed, several studies have shown that the obtained bacterial profiles depend on a number of parameters, such as instrumentation, culture media, and bacterial growth [13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…For instance, the dried sample matrix preparation is inhomogeneous, requiring the selection of "sweet" spots on the target that would give the best ion formation, and matrix adduct ions are often formed that decrease effective mass resolution and decrease the possibility of analyzing low (m/z Ͻ 1000) molecular weight species. Moreover, there are still concerns of spectral reproducibility, owing to the sample preparation steps [14,17,20,21], although some investigations [19,22,23] show that this problem can be overcome.…”
mentioning
confidence: 99%
“…In two studies that were focusing only on the presence or absence of particular peaks but not on peak intensities, the level or reproducibility obtained was equal to 75% or higher using the same mass spectrometer and similar sample preparation techniques (Saenz et al, 1999;Walker et al, 2002). The reproducibility of MALDI-TOF MS fingerprints was high even when mass spectra were obtained from bacterial cultures propagated in the same standard culture conditions during weeks and even months (Bernardo et al, 2002).…”
Section: Intra-laboratory Reproducibilitymentioning
confidence: 98%